Determinants of Compliance with Iron Tablet Consumption Among Pregnant Women in Bengkulu: An Analysis of Knowledge, Occupation, and Demographic Factors - Umami, Desi Aulia (Journal of Current Health Sciences, 2022)
Iron tablets are crucial supplements required during pregnancy to prevent anemia and its complications. However, the coverage of iron tablet consumption among pregnant women at the Sukamerindu Community Health Center in Bengkulu City remains below the national target of 85%, with only 70.98% adhering to this recommendation. This study aims to identify the factors influencing compliance with iron tablet consumption among pregnant women in the region. An analytical observational study with a cross-sectional design was conducted, involving a population of 213 pregnant women with a sample of 101 women selected through accidental sampling. Primary data were collected using a questionnaire. Findings indicate significant effects of knowledge (p=0.000), education (p=0.000), occupation (p=0.000, OR=10.733), parity (p=0.000, OR=7.436), and age (p=0.000, OR=5.800) on compliance. Maternal parity emerged as a dominant factor affecting compliance (p=0.005, OR=6.428). From these results, enhancing pregnant women's knowledge about the importance of regular iron tablet consumption is crucial to reduce complication risks. This study provides essential insights into the dynamics of compliance and suggests the need for more focused approaches to improve compliance levels among pregnant women. Abstrak: Tablet Fe merupakan suplemen penting yang diperlukan selama kehamilan untuk mencegah anemia dan komplikasinya. Namun, cakupan konsumsi tablet Fe di kalangan ibu hamil di Puskesmas Sukamerindu, Kota Bengkulu, masih di bawah target nasional 85%, dengan hanya 70,98% yang mematuhi rekomendasi ini. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang mempengaruhi kepatuhan konsumsi tablet Fe di antara ibu hamil di wilayah tersebut. Sebuah penelitian observasional analitik dengan desain cross-sectional dilakukan, melibatkan populasi 213 ibu hamil dengan sampel 101 wanita yang dipilih melalui sampling aksidental. Data primer dikumpulkan menggunakan kuesioner. Temuan menunjukkan pengaruh signifikan dari pengetahuan (p=0.000), pendidikan (p=0.000), pekerjaan (p=0.000, OR=10.733), paritas (p=0.000, OR=7.436), dan usia (p=0.000, OR=5.800) terhadap kepatuhan. Paritas ibu terungkap sebagai faktor dominan yang mempengaruhi kepatuhan (p=0.005, OR=6.428). Dari hasil ini, meningkatkan pengetahuan ibu hamil tentang pentingnya konsumsi tablet Fe secara rutin diperlukan untuk mengurangi risiko komplikasi. Penelitian ini memberikan wawasan penting tentang dinamika kepatuhan dan menyarankan perlunya pendekatan yang lebih terfokus untuk meningkatkan tingkat kepatuhan di kalangan ibu hamil.